Synthesis, π‐Face‐Selective Aggregation, and π‐Face Chiral Recognition of Configurationally Stable C3‐Symmetric Propeller‐Chiral Molecules with a π‐Core. Issue 19 (15th April 2014) - Saito, Nozomi; Terakawa, Ryo; Yamaguchi, Masahiko
Abstract The C3‐symmetric propeller‐chiral compounds (P, P, P)‐1 and (M, M, M)‐1 with planar π‐cores perpendicular to the C3‐axis were synthesized in optically pure states. (P, P, P)‐1 possesses two distinguishable propeller‐chiral π‐faces with rims of different heights named the (P/L)‐face and (P/H)‐face. Each face is configurationally stable because of the rigid structure of the helicenes contained in the π‐core. (P, P, P)‐1 formed dimeric aggregates in organic solutions as indicated by the results of 1H NMR, CD, and UV/Vis spectroscopy and vapor pressure osmometry analyses. The (P/L)/(P/L) interactions were observed in the solid state by single‐crystal X‐ray analysis, and they were also predominant over the (P/H)/(P/H) and (P/L)/(P/H) interactions in solution, as indicated by the results of 1H and 2D NMR spectroscopy analyses. The dimerization constant was obtained for a racemic mixture, which showed that the heterochiral (P, P, P)‐1/(M, M, M)‐1 interactions were much weaker than the homochiral (P, P, P)‐1/(P, P, P)‐1 interactions. The results indicated that the propeller‐chiral (P/L)‐face interacts with the (P/L)‐face more strongly than with the (P/H)‐face, (M/L)‐face, and (M/H)‐face. The study showed the π‐face‐selective aggregation and π‐face chiral recognition of the configurationally stable propeller‐chiral molecules.